Flask : building Python web services : unleash the full potential of the Flask web framework by creating small to large and powerful web applications : a course three modules.: building Python web services : unleash the full potential of the Flask web framework by creating small to large and powerful web applications : a course three modules. (2017) - Dwyer, Gareth; Aggarwal, Shalabh; Stouffer, Jack
No abstract available